AB0603 Periodontal Disease is Common in Patients with Systemic Lupus Erythemathosus. (9th June 2015) - de Pablo, P.; Dewan, K.; Dietrich, T.; Chapple, I.; Gordon, C.
Abstract : Background: Periodontal disease is a common chronic inflammatory disease that has been associated with rheumatoid arthritis and a potential causal role has been suggested. However, data on the prevalence of periodontal disease in patients with systemic lupus erythematosus (SLE) are scarce. Objectives: To investigate the prevalence of periodontal disease in patients with systemic lupus erythematosus and compare it to that of the general population. Methods: We examined the periodontal status in dentate patients with SLE who met the ACR criteria for SLE. Mild periodontitis was defined as having at least one periodontal probing depth of 4+mm. Severe periodontitis was defined as having at least one periodontal probing depth of 6+mm. We compared the prevalence of periodontal disease in SLE patients with that of a geographically matched dentate sub-sample of the Adult Dental Health Survey (ADHS), West Midlands, a representative population survey in the UK (reference group). Age-standardized prevalence estimates were calculated and logistic regression was used to evaluate the association between SLE and periodontal disease adjusting for age and sex. Results: We examined a total of 105 individuals with SLE, with a mean age of 45.6 years (IQR 36-56), of whom 98 (92%) were women. The reference group included 484 participants, with a mean age of 48.9 years (IQR 36-63), of whom 271 (56%) were women. The age-standardised prevalence of periodontitis was 85% (95% CI: 79% to 92%) in SLE patients, compared with 55% (95% CI: 51% to 60%) in the general West Midlands population. After adjustments for age and sex, patients with SLE were significantly more likely to have periodontitis than ADHS participants (OR 7.25, 95% CI 3.84 to 13.68). Results were similar when analyses were restricted to women only (OR 7.51, 95% CI: 3.85 to 14.64). The age-standardised prevalence of severe periodontitis was 11% (95% CI: 5% to 18%) in patients with SLE and 11% (95% CI: 8% to 14%) in the West Midlands population. No significant association of SLE with severe periodontitis was observed (OR 1.15, 95% CI: 0.56 to 2.36). Conclusions: Our data suggests that periodontal disease is more common among individuals with SLE compared to a representative geographically matched sample. However, the prevalence of severe periodontal disease is similar between SLE and the general population. Further studies are necessary to confirm the possible association between periodontitis and SLE. Disclosure of Interest: None declared